2015
DOI: 10.14411/fp.2015.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between latent toxoplasmosis and clinical course of schizophrenia - continuous course of the disease is characteristic for Toxoplasma gondii-infected patients

Abstract: The aim of the present study was to investigate the association between various clinical aspects of schizophrenia and seropositivity against Toxoplasma gondii (Nicolle et Manceaux, 1908). We selected 94 patients with schizophrenia and investigated the seropositivity rate for anti-T. gondii IgG antibodies by ELISA. Clinical parameters of schizophrenic patients such as illness type and status, clinical course, awareness of the illness and need for electroconvulsive therapy (ECT) were compared with their serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…It has even been documented that the changes in brain morphology that are characteristic of schizophrenia, such as gray matter reduction in frontal and temporal cortices, caudate, median cingulate, and thalamus, are in fact typical for Toxoplasma-seropositive schizophrenia patients (6). Congruently, the Toxoplasma-seropositive patients express more prominent positive symptoms of schizophrenia (7,8) and have a 15-times higher probability of having a continuous course of disease than the Toxoplasma-free patients (9). Far fewer studies have shown the association of toxoplasmosis with other mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has even been documented that the changes in brain morphology that are characteristic of schizophrenia, such as gray matter reduction in frontal and temporal cortices, caudate, median cingulate, and thalamus, are in fact typical for Toxoplasma-seropositive schizophrenia patients (6). Congruently, the Toxoplasma-seropositive patients express more prominent positive symptoms of schizophrenia (7,8) and have a 15-times higher probability of having a continuous course of disease than the Toxoplasma-free patients (9). Far fewer studies have shown the association of toxoplasmosis with other mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding schizophrenia, the clinical picture of schizophrenia in toxoplasma‐infected and toxoplasma‐free patients differs in several respects. Toxoplasma‐infected individuals show more severe positive symptoms of schizophrenia and are more likely to experience a continuous course of disease than toxoplasma‐free patients . Several studies investigating the relationship between T. gondii and suicide in infected persons or in patients with schizophrenia gave inconclusive results .…”
Section: Introductionmentioning
confidence: 99%
“…gondii infection has been associated with symptom severity in schizophrenia 23,27,28 . In addition, latent toxoplasmosis may have a negative impact on the disease course and treatment response in patients with schizophrenia 29 . Corroborating these clinical data, patients with schizophrenia T. gondii-seropositive presented more significant morphological changes in the caudate, cingulate, thalamus and occipital cortex in comparison with seronegative patients 30 .…”
Section: Discussionmentioning
confidence: 99%